Borescopes as a Training Tool for Neuroendoscopy - Aman Bakhsh; Jitin Bajaj; Mansi Yadav; Jayant Patidar; Shailendra Ratre; Vijay S. Parihar; Yad R. Yadav (Indian Journal of Neurosurgery)
Background Neuroendoscopy is increasingly utilized as a minimally invasive method. Due to its challenging learning process, there is a pressing need for cost-efficient training methods for residents and fellows in these surgeries. One such modality is using borescopes as substitutes for endoscopes, which could prove beneficial in resource-limited settings. However, existing literature on the use of borescopes in surgical practice for training remains scarce.